SPECIFIC ASPECTS OF ALAIN`S TEACHING ACTIVITY - Martianova, Mariia (Educological discourse, 2019)
The article deals with the specific aspects of the teaching activity of the French teacher of philosophy Alain (Emily-Auguste Chartier). The scholar emphasized the importance of the influence of family education in the formation of the individual and added the necessity of strict education. According to Alain`s theory, school helps the child to reveal their natural abilities independently of their family ties. The main literary genre (propos), which the scientist used to write his ideas, is highlighted. The scientist underlined the usefulness of writing such works as essays and reflections on the given topic, where students learn to express their thoughts correctly and intelligently, overcome the fear of public speaking. The philosopher added that a class also influence on educational process, that is why he preferred the absence of additional learning material on the walls as they distract student’s attention. It is defined that children develop their natural abilities, learn to cope even with those tasks that initially cause rejection and a desire to retreat, due to hard-working nature. It is emphasized that studying of masterpieces, taking into consideration the experience of previous generations, their knowledge about human nature, the relationship between personality and the surrounding world is very important for formation of healthy and intellectual society. The basic principles of teaching, which were guided by the French teacher, such as the principle of diligence, the principle of freedom of thought, the principle of respect and detailed analysis of the works of famous scholars and writers, and the principle of the connection of learning with life, are determined. These principles are possible only with the presence of a teacher who has professional qualities, the desire to direct his students to work and the aspiration to learn and study the necessary information for their adult life.